Synthesis, characterization and biological activities of monometallic and bimetallic nanoparticles using Mirabilis jalapa leaf extract - Sumbal; Asifa Nadeem; Sania Naz; Joham Sarfraz Ali; Abdul Mannan; Muhammad Zia (Biotechnology Reports, 2019)
Monometallic ZnO and Ag nanoparticles (NPs) and bimetallic ZnO/Ag NPs were synthesized using leaves extract of Mirabilis jalapa. XRD analysis confirmed the crystalline nature of NPs with size range from 19.3 to 67.4 nm for bimetallic, and 12.9 and 32.8 nm for monometallic NPs. SEM images reveal varying shapes of the monometallic (needle like and spherical for ZnO and Ag, respectively) and bimetallic (plates, sheets, and spherical) NPs depending upon concentration of salts used. Biological characterization reveals that both mono and bi metallic nanoparticles demonstrate free radical scavenging, total antioxidant, and reducing power potentials. Phenolic and flavonoid like properties of NPs were also observed might be due to presence of different functional groups on the particles surface. Bimetallic NPs displayed astonishing antibacterial (up to 25 mm zone of inhibition) and antileishmanial properties. The results suggest that bimetallic ZnO/Ag nanoparticles hold greater potential then monometallic against bacteria and Leishmania. Other biomedical applications also varied depending upon concentration of precursors. Furthermore, ratio of salt concentrations used for synthesis of bimetallic NPs affect morphological and biochemical characteristics of NPs. Keywords: M. jalapa monometallic, Bimetallic, Biological properties, Nanoparticles